Evolution of hydraulic property and crack propagation of mine roof strata during bending-splitting deformation - Jiajun Wang; Jiangzhan Chen; Jiacheng Lin; Jiangtao Ren (Scientific Reports)
Abstract To explore the mechanism of water inrush from the mine roof strata, a series of seepage-acoustic emission (SAE) experiments on red sandstone disc samples were carried out. The effects of the height to diameter ratio (H/D) and pore pressure on the mechanical, hydraulic and crack propagation properties of red sandstones were investigated. Test results show that, the peak load of rock samples declines with the decreasing H/D and increasing pore pressure. The seepage process can be divided into three phases, i.e., lower permeability stage, and permeability fluctuation stage and high permeability stage. The crack propagation mainly appears near and after the peak load. In addition, in the low permeability stage, fluid mainly flows through the pores of rock. With the deformation and crack propagation, the fluid enters the cracks, causing fluctuations in permeability. When penetrating cracks forms, a large amount of fluid passes through the cracks, causing a rapid increase in permeability. In the case of high H/D, the water inrush phenomenon obviously lags behind the rock failure, and this lagging phenomenon becomes more significant as the water pressure decreases. The critical displacement (the displacement corresponding to the time of water inrush) can be used to characterize the risk of water inrush. The lower the H/D, the greater the water pressure and the higher water inrush risk. Therefore, it is necessary to control the distance from the working face to the overburden aquifer and reduce the groundwater pressure, so as to reduce the risk of water inrush from the roof.